Application of function-oriented modelling systems in construction control implementation - A. A. Lapidus; A. Yu. Shchukin (Vestnik MGSU)
Introduction. The study of functional dependencies between the main participants of construction control, such as technical customer, general contractor and general designer, is carried out.Materials and methods. The structure of their interaction is presented in the form of a flowchart, which is drawn up using function-oriented analysis methodology. Presentation of information in the form of a flowchart makes it possible to analyze the interaction of participants at each stage of construction control. Also, integration of IDEF0 modelling method allows to analyze and correct the relationships between functional blocks.Results. Construction control decomposition is created by forming functional blocks, which consist of the main stages of construction control realization. Then a complex decomposition of these blocks is performed, which allows us to obtain a “micro-level” of each of the main blocks. This approach to the formation of interrelationships between the main participants of construction control will subsequently allow to identify the main problems that are encountered at the stage of control and will help to improve the efficiency and structuring of the construction control system.Conclusions. It is proposed to take a new look at construction control from the point of view of functional interaction of control participants, which in the future will lead to a reduction in the number of poor-quality construction products or operations.